The role of social media in clubfoot: information sharing and social support. (2021) - Hanna, Gabriel; Batko, Brian D.; Potter, James; Ippolito, Joseph; Edobor-Osula, Folorunsho
Abstract : Purpose: Clubfoot is the most common congenital foot deformity in children. Caregivers often seek medical information on the internet. The aim of the study was to characterize how social media is used by caregivers to access medical information. Methods: A search was performed on Facebook, Twitter and YouTube platforms. Information was quantitatively assessed. Comments were qualitatively assessed, and the Kruskal-Wallis test was used to study thematic comment distribution. Results: In total, 58 Facebook groups and pages, 109 YouTube accounts and ten Twitter accounts related to clubfoot were discovered from 2007 to 2019. Facebook groups and pages had a collective 56 123 members and 80 544 total likes, respectively. YouTube had a collective 3 280 454 views, with 54 969 total comments throughout the accounts. Comment themes most commonly included sharing information and advice (38.7%), appreciation and success stories (12.8%), emotional support (12.7%) and social media as a second opinion (11.9%). Facebook groups contained a significantly higher number of comments related to 'social media as a second opinion' compared with Facebook pages (p = 0.001), Twitter (p = 0.016) and YouTube (p < 0.0001) while YouTube contained a significantly lower number of comments related to 'sharing information' compared with Facebook groups, pages and Twitter (p < 0.0001). Conclusion: Social media continues to be a growing tool for information sharing and the findings of this study highlight the importance placed by caregivers on the advice of their peers. The online presence of caregivers may represent an opportunity for orthopaedic surgeons to communicate with patients and help them make informed decisions. Level of evidence: IV